1991
DOI: 10.1103/physrevd.44.1585
|View full text |Cite
|
Sign up to set email alerts
|

Mesons as bilocal fields in the harmonic approximation: A reassessment

Abstract: The spectrum and lepton decay constants of the pion, the kaon, and their radial excitations, as well as the pion decay width in two photons, are computed in a recently proposed framework that combines the bilocal approach to mesons and the potential method treated covariantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Its four chief virtues, however, are (i) that it satisfies the Ward-Takahashi identity (21), (ii) that it reduces to the bare vertex in the free-field limit as must be in perturbation theory, (iii) that its transformation properties under Lorentz transformations and charge conjugation are the same as for the bare vertex, and (iv) it has no kinematic singularities. It is important to note that the correct axial-anomaly result cannot be obtained [11] analytically in the chiral limit unless a quark-photon-quark (qqγ) vertex that satisfies the Ward-Takahashi identity is used (even if DχSB is employed and the pion does appear as a Goldstone boson, as comparison with [54,55] shows).…”
Section: Bound States Of Dynamically Dressed Constituent Quarksmentioning
confidence: 99%
“…Its four chief virtues, however, are (i) that it satisfies the Ward-Takahashi identity (21), (ii) that it reduces to the bare vertex in the free-field limit as must be in perturbation theory, (iii) that its transformation properties under Lorentz transformations and charge conjugation are the same as for the bare vertex, and (iv) it has no kinematic singularities. It is important to note that the correct axial-anomaly result cannot be obtained [11] analytically in the chiral limit unless a quark-photon-quark (qqγ) vertex that satisfies the Ward-Takahashi identity is used (even if DχSB is employed and the pion does appear as a Goldstone boson, as comparison with [54,55] shows).…”
Section: Bound States Of Dynamically Dressed Constituent Quarksmentioning
confidence: 99%
“…Of course, with another choice of V 0 and m q , one can achieve much better agreement for meson decays if one accepts meson masses which are several times too high, as shown in [6] on the example of the pion. However, as already remarked above, the problems of accounting quantitatively for the hadronic structure and decays within the bound-state approach are out of scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the hadronic matrix elements of the above effective operators (2)-(6), we use the variant [8,9] of an effective meson bilocal theory [9][10][11][12] in which the related decay π 0 → γγ was computed by two of us [6], along with the pion and kaon spectrum and the decay constants 2 F π and F K . Varying the effective bilocal action yields [9][10][11][12]7] the Schwinger-Dyson equation (SDE) for the dressed quark propagator (whose self-mass Σ(q) is thereby generated dynamically), and the Bethe-Salpeter equation (BSE) for the bilocal bound-state meson-vertex function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the V-shaped potential γ |y| withṼ (y) leads to a singular funnel shaped potential. We remind the reader that, although the term ''funnel potential'' (or ''funnel interaction'') was coined in meson physics with reference to the central potential V (r) = ar − b/r in three dimensions (see [51][52][53]), it has later been used, referring to different potentials, in other areas of physics (see [54][55][56]). It is noteworthy that while there is no ambiguity as to the meaning of the δ-interaction, there have been different interpretations of the meaning of the δ ′ -interaction in the literature on the subject (see [57] for a thorough critical review of the various interpretations found in the relevant literature).…”
Section: Introductionmentioning
confidence: 99%